Current and future indications for cardiac pacing: follow-up of the pacemaker patient - Martins, Vítor Paulo (2000)
Objectifs: To review the indications of permanent cardiac pacing, focusing on essentials aspects of follow-up of patients with pacemaker, namely the detection of dysfunctions, complications, and electromagnetic interferences. Methods: critical review of the literature. Conclusions: The current indications for cardiac pacing are no longer restricted to the classical ones, being today a reality in some situations related to obstructive hypertrophic cardiomyopathy, heart failure, neurally mediated syncope and atrial fibrillation prevention. Some controversy subsists though, specially in defining the subgroups which benefit this therapy the most.Generators implanted today are small, have low energy consumption and increased longevity. Contemporary leads also have small calibre, high flexibility and durability, being steroid-eluting, which allows simpler and faster interventions and fine chronic pacing thresholds. Pacemaker follow-up should be accomplished by cardiac pacing specialised physicians, in order to take advantage of all the diagnostic and therapeutic functions available in the contemporary generators. The non-cardiologist physician´s role consists in the exclusion of all situations that might traduce pacing disfunction. Therefore, the author describes a number of signs and symptoms usually referred by patients and their relative importance, and enunciates the most frequent complications in permanent cardiac pacing and the subsequent adequate procedures.Electromagnetic interferences are unfrequent and mostly transient, although they may be potencially catastrophic in pacing dependent patients after prolonged exposure and under certain circunstances. Some specific situations are reviewed, particularly the issue of the use of cellular phones. It is now believed that their use is not contraindicated as long as a 15 cm security distance is kept between the generator and the cellular phone.